The Heirs of Avicenna: Philosophy in the Islamic East, 12-13th Centuries: Metaphysics and Theology - Adamson, Peter (Islamicate intellectual history, 2023)
This is the first in a series of sourcebooks charting the reception of Avicenna (Ibn Sīnā, d.1037) in the Islamic East (from Syria to central Asia) in the 12th-13th centuries CE. Avicenna was the dominant philosophical authority in this period, who provoked generations of thinkers to subtle critique, defense, and development of his ideas. The series will translate and analyze hundreds of passages from works by such figures as al-Ghazālī, al-Suhrawardī, Fakhr al-Dīn al-Rāzī, Naṣīr al-Dīn al-Ṭūsī, and many more. This volume focuses especially on issues in metaphysics, dealing with topics like the essence-existence distinction, the problem of universals, free will and determinism, Platonic Forms, good and evil, proofs of God’s existence, and the relationship between philosophy and theology